2006
DOI: 10.1097/01.jsm.0000244611.57548.40
|View full text |Cite
|
Sign up to set email alerts
|

Adequacies of Skin Puncture for Evaluating Biochemical and Hematological Blood Parameters in Athletes

Abstract: Skin puncture is a reliable, easy, accurate, and less invasive sampling method for assessing hematological and some biochemical parameters in athletes, respecting that blood samples should always be obtained from the same site, especially in follow-up studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
10
0
4
Order By: Relevance
“…La correcta interpretación de la analítica sanguínea supone distinguir entre a) los procesos de adaptación normal a la actividad física y b) los valores que pueden significar un mayor riesgo de sufrir procesos patológicos o procesos no adaptativos 11,12 .…”
Section: Evaluación Del Estado Proteico Visceralunclassified
See 2 more Smart Citations
“…La correcta interpretación de la analítica sanguínea supone distinguir entre a) los procesos de adaptación normal a la actividad física y b) los valores que pueden significar un mayor riesgo de sufrir procesos patológicos o procesos no adaptativos 11,12 .…”
Section: Evaluación Del Estado Proteico Visceralunclassified
“…En casos de dé-ficit extremo, se pueden producir lesiones cardiovasculares, musculares y renales de tipo irreversible. El ejercicio modi-y al final del periodo de entrenamiento para poder valorar objetivamente el aumento de los glóbulos rojos y la eficacia de los entrenamientos a nivel hematológico 11 . Como norma general, las pruebas hematológicas suelen pedirse en cada una de las 3 fases de la temporada: periodo preparatorio general, periodo específico y periodo competitivo, sobre todo si se trata de deportes de resistencia de larga duración y, más aún, cuando el deportista sea mujer y el deporte de gran impacto 38 .…”
Section: Potasio (K +unclassified
See 1 more Smart Citation
“…A previous article from our laboratory demonstrated that fingerprick may be an interesting alternative to venipuncture (44) . This technique is less invasive and less stressful, enabling the monitoring of athletes during and after physical tests, training or competition, without major changes in routine.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is less invasive and less stressful, enabling the monitoring of athletes during and after physical tests, training or competition, without major changes in routine. Furthermore, the currently available automated pieces of equipment allow the use of increasingly lower sample volumes, enabling the analysis of blood samples in microtubes (44) . However, some individuals have reported some discomfort with the procedure.…”
Section: Introductionmentioning
confidence: 99%